Revealing the origin of dislocations in Pb1−xSb2x/3Se (0 < x ≤ 0.07). Issue 37 (22nd September 2020) - Nan, Pengfei; Chang, Yunjie; Chen, Zhiwei; Pei, Yanzhong; Zhang, Yongsheng; Wang, Yumei; Ge, Binghui
Abstract : Dislocations could be originated from the nanostructures in Pb1− x Sb2 x /3 Se (0 < x ≤ 0.07), which is important to defect engineering in thermoelectrics. Abstract : Defect engineering is an effective route to improve the performance of thermoelectric materials, including Sb doped PbSe, but the formation mechanism of defects remains unclear. In the thermoelectric material Pb1− x Sb2 x /3 Se (0 < x ≤ 0.07), a large number of dislocations have been reported, and they enhance intermediate-frequency phonon scattering, thereby improving the zT value. However, the microstructural origin of dislocations remains unclear. In this paper, via a combination of atomic resolution scanning transmission electron microscopy and density functional theory, we successfully revealed the microstructure of Pb1− x Sb2 x /3 Se ( x = 0–0.07) for in-depth understanding of the formation mechanism of dislocations. Plenty of zinc blende (ZB) nanostructures are found in the PbSe matrix with a rock salt (RS) structure, and the theoretical calculations confirm its viability from the point of view of formation energy. A similar ZB structure is identified in the dislocation cores of Sb-doped materials as well, and thus the formation mechanism of dislocations is discussed for this PbSe system. This result provides important guidance to understand the structural evolution in compounds with a RS structure, especially in high-performance lead chalcogenide thermoelectric materials.